Effectively communicating developmental system reliability growth plans and risk. Issue 1 (31st December 2022) - Nation, Paul; Wayne, Martin; Modarres, Mohammad
ABSTRACT: Engineers may be technically competent; however, some lack the communication skills necessary to transfer information and reason. This situation makes excellent technical skills superfluous. In this paper, communication is reviewed from a reliability engineering viewpoint, discussing why conveying well-crafted information to decision-makers is pivotal to success. Firstly, the authors examine several engineering communication myths. The authors then present how good communication fundamentals can be used to meet the decision-maker requirements leading to the desired engineering outcomes. Next, the authors narrow the scope to examine presenting reliability growth plans and their associated risk to decision-makers from a reliability engineering perspective. The paper concludes with an analysis of the robustness of reliability estimates and why distribution or interval estimators should always be preferable to point estimators when describing reliability metrics. While the paper focuses on reliability engineering practitioners and their efforts, the content is helpful for other engineering specialists when considering communication.